Проблеми управління трудовим потенціалом промислових регіонів України - Новіков, Д. А. (НТУ "ХПІ", 2015)
В статті розглянуто проблеми управління трудовим потенціалом промислових регіонів України, обґрунтовано джерела їх виникнення та шляхи усунення на основі поєднання основних функцій управління трудовим потенціалом та регіональних галузей промисловості як об’єктів управління. Доведено, що регіони України мають потужний потенціал промислового розвитку, який може бути реалізований за умови раціонального використання виробничих ресурсів шляхом ефективного управління трудовим потенціалом.

The problems of labor potential management in industrial region of Ukraine are considered in the article. The sources of their origin and ways of their eliminating are justified based on a combination of the basic functions of labor potential management and regional industries as objects of management. The complex of measures to improve the management, developed by the territorial authorities, should include improving the first two groups of functions. By the last group of functions of territorial authorities must offer reasonable solutions Central and sectoral authorities. Thus, a subsystem management functions of the employment potential of industrial regions. Using data presented at the fourth level of the tree purposes, gives you the opportunity to get more information about the content of individual management functions. You then need to analyze the execution results of the formulated control functions depending on the performance of the subject of management, basic management principles, the correctness of the chosen methods and adequacy of resources. It is necessary to rely on the Statute of the territorial government, current regulations, conductsystematic monitoring of the performance management system labour potential to determine the effectiveness of each management function. Directions for further research related to the development of methods of monitoring the effectiveness of the system of management of labour potential industrial regions of Ukraine.
Management problems of the labour potential of the industrial regions of Ukraine
Keywords: промислове виробництво; виробничий потенціал; функції управління; органи територіального управління; industrial regions of Ukraine; labor potential; management of human potential; management functions